2022
DOI: 10.1073/pnas.2209729119
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite evades mosquito immunity by glutaminyl cyclase–mediated posttranslational protein modification

Abstract: Glutaminyl cyclase (QC) modifies N-terminal glutamine or glutamic acid residues of target proteins into cyclic pyroglutamic acid (pGlu). Here, we report the biochemical and functional analysis of Plasmodium QC. We show that sporozoites of QC-null mutants of rodent and human malaria parasites are recognized by the mosquito immune system and melanized when they reach the hemocoel. Detailed analyses of rodent malaria QC-null mutants showed that sporozoite numbers in salivary glands are red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Studies have shown that conformational changes or posttranslational modification (glutaminyl cyclase) of this surface protein prevents the melanization of oocysts and sporozoites of Plasmodium . 21 , 22 In the case of P. vivax , although it may evade the immunological response of An . darlingi , the vector’s ability to melanize free sporozoites in the hemocoel could be important in decreasing the transmission success of P. vivax .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that conformational changes or posttranslational modification (glutaminyl cyclase) of this surface protein prevents the melanization of oocysts and sporozoites of Plasmodium . 21 , 22 In the case of P. vivax , although it may evade the immunological response of An . darlingi , the vector’s ability to melanize free sporozoites in the hemocoel could be important in decreasing the transmission success of P. vivax .…”
Section: Discussionmentioning
confidence: 99%
“…The size and genetic complexity of Pf allows it during each infection to present thousands of elusive Ags, while in human host alone, the parasite changes the antigenic proteins at each life stage. In addition, the parasite has developed a series of strategies that allow it to confuse, hide, and misdirect the human immune system, [175] engendering additional difficulty in choosing vaccine Ag.…”
Section: 21mentioning
confidence: 99%
“…When the CSP’s glutaminyl cyclase target (glutamine) was subjected to mutation, a corresponding melanization of the sporozoites was observed. Hence the glutaminyl cyclase can be another druggable target (Kolli et al 2022 ). Several other proteins, such as TRAP, MSP, and others, have been reported to play critical roles in parasite evasions (Nakayama et al 2021 ).…”
Section: Malaria Parasite Survival Starts From the Mosquito Host — Ho...mentioning
confidence: 99%